The teachers’ evolving role in mitigating violent extremism in Kenyan secondary schools - John Njeru Maringa; Garai Imre; György Mészáros (Discover Education)
Abstract Violent Extremism is of great concern to the world today. Many countries, while formulating policies to combat violent extremism, look only to military force and surveillance (hard power) that deal with already radicalized individuals. In recent years, Kenya has experienced a plethora of terrorist attacks as young people continue to become both victims and perpetrators of violent extremism. This study has established that in some parts of Kenya, like the north-eastern and Coast regions, young men and women have been drawn to the extremist ideology of al Shabaab and have joined the group as active members, creating a social problem for their families and communities. This has affected learning in some of the schools, as some students have been targets for recruitment through the established local recruitment networks. In this paper, we explore transformational violent extremism on how educators can help prevent radicalization by countering the ideological appeal of terrorists’ narratives on students’ emotional, intellectual, and psychological levels (soft power). According to President Obama, “Ideologies are not defeated by guns, but by new ideas.”